Pengenalan Literasi Keuangan Digital Pada Generasi Z di SMK Assa’adah Bungah Gresik - M. Nasyah Agus Saputra; KH. Muhammad Alauddin; Dwi Afrianti; Niswatun Hasanah; Fri Haendid Alfiyan; Martha Hermina Zaytun (Abdimas Indonesian Journal, 2024)
The rapid development of financial technology has intensified the use of digital financial services among Generation Z. However, this trend is not fully accompanied by adequate financial management capabilities, resulting in a gap between technological access and financial literacy. This community service activity aims to enhance digital financial literacy among twelfth-grade students at SMK Assa’adah Bungah Gresik in order to foster rational, adaptive, and long-term financial behavior. The study employs an educational and participatory approach through the delivery of instructional materials, interactive discussions, and experience-sharing activities involving university students as facilitators of contextual learning. The findings indicate that although students demonstrate a high level of familiarity with digital financial services, their understanding remains largely limited to technical aspects and has not fully encompassed conceptual dimensions such as financial planning and the control of consumptive behavior. Post-activity evaluation reveals an improvement in students’ financial understanding and awareness. These results confirm that the educational and participatory approach is effective in bridging the gap between the use of financial technology and financial management capabilities. Overall, this activity contributes to strengthening the financial readiness of vocational high school students as part of Generation Z in facing the challenges of the digital economy and highlights the importance of developing sustainable, contextual, and experience-based digital financial literacy programs.